2023
DOI: 10.1111/1744-7917.13160
|View full text |Cite
|
Sign up to set email alerts
|

The piRNA pathway is required for nucleopolyhedrovirus replication in Lepidoptera

Abstract: The Piwi‐interacting RNA (piRNA) pathway has been shown to be involved in the antiviral defense against RNA viruses, especially in mosquitoes, but its universality has been questioned. Here, we used the Bombyx mori nucleopolyhedrovirus (BmNPV) ‐infected silkworm as a model to explore the effects of the key factors of piRNA pathway, BmAgo3 and Siwi, on replication of a large DNA virus (belonging to the family of Baculoviridae). We demonstrated that BmAgo3 and Siwi could promote the replication of BmNPV through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Regulatory non-coding RNAs can be divided into short, medium, and long non-coding RNAs according to different lengths. Short-stranded noncoding RNAs mainly include piRNA, siRNA, and miRNA ( Feng et al, 2021 ; Xia et al, 2022 ). The three are similar in length but work in different ways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulatory non-coding RNAs can be divided into short, medium, and long non-coding RNAs according to different lengths. Short-stranded noncoding RNAs mainly include piRNA, siRNA, and miRNA ( Feng et al, 2021 ; Xia et al, 2022 ). The three are similar in length but work in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…The three are similar in length but work in different ways. piRNA mainly interacts with the piwi protein and mediates the silencing of transposon genes ( Feng et al, 2021 ; Xia et al, 2022 ); siRNA, on the other hand, as double-stranded RNA, binds in vivo to become RISC complexes, silences target genes, often imported by foreign genes, may be viruses ( Zhao S. et al, 2022 ). While microRNAs are mainly synthesized in the nucleus, where precursor genes are first cleaved by the Drosha enzyme to form precursor miRNA (pri-miRNA), which is then transported out of the nucleus by Exportin 5, and finally cleaved by the Dicer enzyme in the cytoplasm to form mature miRNA ( MacRae et al, 2006 ), miRNA is also related to RISC complexes, it is a single strand, and binding to the target gene only exists at the 3′ end, siRNA can bind and silence the target gene in all segments of the gene.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, an antisense piRNA that targets Siwi becomes downregulated during BmNPV infection, reinforcing the idea of an active involvement of the piRNA pathway during BmNPV infection [ 203 ]. In concordance with this, knockdown and over-expression studies indicated that Siwi and BmAgo3 can promote BmNPV replication in silkworm cells, which is, however, consistent with a proviral instead of an antiviral role [ 204 ]. During baculovirus infection, a reorganization of the cellular nuclear chromatin takes place concomitant with the formation of the virogenic stroma, the site of virus genome DNA replication [ 205 , 206 ].…”
Section: Insights From Research On Piwi Proteins and Pirnas In The Si...mentioning
confidence: 73%
“…While in mammals the role of the piRNA pathway in the regulation of cancer cell function has received wide interest [ 278 ], its involvement in virus infection remains understudied [ 279 ], which could be related to the preferential expression of Piwi proteins in the germline [ 280 ]. Interestingly, the Piwi proteins Aub and Ago3 have recently been shown to have a proviral role during the infection of BmNPV ( Baculoviridae ) in silkworm larvae (discussed in Section 4.4 ; [ 204 ]). It can be speculated that the Piwi proteins have a role in the stabilization of transposon mobilization that could interfere with faithful viral genome replication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation